Analysis of Reading Comprehension Skills of Grade III Students through Problem based Learning (PBL) Model - Shefa Salsa Aulia; Research, Mudzanatun; Untari, Mei Fita Asri (Interdisciplinary Journal of Social Science and Education (IJSSE), 2024)
This study aims to analyze the reading comprehension abilities of class III students at SDN Gayamsari 01 Semarang through the Problem Based Learning (PBL) model and what factors support and inhibit students' reading comprehension abilities. This type of research is qualitative research. The subjects in this research were class III students and class III teachers at SDN Gayamsari 01 Semarang. Data collection techniques were carried out using observation, interviews and documentation. The results of the research show that the majority of class III students at SDN Gayamsari 01 Semarang have good reading comprehension skills, reading comprehension through the Problem Based Learning (PBL) model is able to support students to build their own knowledge through direct experience with the group in understanding the content of reading, on reading ability Comprehension can be seen how students are able to absorb information and understand the content of the reading. Supporting and inhibiting factors for students reading comprehension abilities, namely supporting factors include intellectual factors, environmental factors, psychological factors and physiological factors. Meanwhile, inhibiting factors are students’ knowledge and experience, students reading habits, interest in reading, and the reading materials that students.